Male Neighborsâ Behavior: Bystander Effect in Domestic Violence Cases - Wardana, Nido Dipo; Margaretha, Margaretha (Journal of Educational, Health and Community Psychology, 2018)
This research was twofold and aimed to explore male neighborsâ behavior as bystanders of domestic violence (DV) cases. Study 1 used survey on 94 male respondents to obtain description about bystander behavior and examine the relationship between situational barriers, neighborhood cohesion, and bystanderâs intention to help victims. Study 2 used qualitative approach with instrumental case study, involving three male participants to understand the dynamic of bystander effect on male neighbors who had witnessed DV. Bystander effect (BS) is a phenomenon in which individual is less likely to intervene in an emergency if bystander present. BS was analyzed based on three root psychological processes, namely: diffusion of responsibility, audience inhibition, and pluralistic ignorance; the three appeared in the bystander intervention stages. An important finding was the role of neighborhood cohesion which interacted with DV-supporting norm; such that bystanders from highly cohesive neighborhood were resistant to help victims of real DV cases although social cohesion was a notable predictor of intention to help. The evidences in this research expanded LatanÃ©âs (1981) theory of social impact as well as supporting Levine (1999) and Banyard and colleaguesâ (2004) notion of distorted thinking as a root of bystander inaction. Implication of the findings for community-based interventions is discussed.